Evaluacion de variedades promisorias de frijol (P. vulgaris) a la incidencia de "telarana" o "mustia" - Mora, B.E.; Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1979)
CIATs collection of promising bean lines was evaluated over a 2- mo period for resistance to web blight (Rhizoctonia microsclerotia) on a highly infested soil in Esparza, Costa Rica, where conditions are very favorable for the development of this disease. A scale of 1-5 was used, based on the percentage of dead leaf area. Only P. 368 and P .740 showed some tolerance to the fungus. (AS)